Plug-In Hybrid Electric Bus Energy Management Based on Dynamic Programming. (December 2016) - Xie, Shanshan; Sun, Fengchun; He, Hongwen; Peng, Jiankun
Abstract: An energy management strategy based on dynamic programming for a plug-in serial-parallel hybrid electric bus is proposed. The sets of comprehensive cost function, five control variables and mesh accuracies are illustrated. Then the fuel economy is discussed, followed by the sensitivity analysis of this strategy on different lengths of driving cycle input and dissimilar control variable settings. It can be concluded that scaling the length of driving cycle and battery capacity have little effect on control laws output while optimum control variable settings should combine exact characters of driving cycles and driving components of the bus.